Transgenic double‐stranded RNA rice, a potential strategy for controlling striped stem borer (Chilo suppressalis). Issue 2 (4th December 2021) - Mao, Cui; Zhu, Xiaoping; Wang, Peipei; Sun, Yajie; Huang, Renliang; Zhao, Mingchao; Hull, J Joe; Lin, Yongjun; Zhou, Fei; Chen, Hao; Ma, Weihua
Abstract: BACKGROUND: Although the striped stem borer (SSB, Chilo suppressalis Walker) is a devastating pest of rice that causes significant economic losses, management options are currently limited. Plant‐mediated RNA interference (RNAi) is an emerging crop protection technique in which transgenic plants are modified to express insect‐specific double‐stranded RNAs (dsRNAs) that trigger RNAi silencing in target pests. RESULT: In this study, an RNAi‐based screen of 35 candidate SSB genes identified a small heat shock protein gene ( CssHsp ) as a potential plant‐based RNAi target. To assess its utility in planta, a total of 39 transgenic rice plants were generated, with 11 independent transformants found to contain a single copy of the ds CssHsp expression cassette. In life‐time feeding bioassays, three transgenic lines (DS10, DS35, DS36) were found to have significant negative impacts on SSB populations. After feeding for 8 days, mortality in the three transgenic lines exceeded 60%. By pupation, mortality further increased to 90% and few SSB survived to eclosion. Gene expression analyses confirmed that CssHsp transcript levels were significantly reduced after feeding on the transgenic ds CssHsp rice. CONCLUSION: These results demonstrate the potential for developing a plant‐mediated RNAi strategy targeting CssHsp as a more biorational field‐based approach for SSB control. © 2021 Society of Chemical Industry. Abstract : Silencing the CssHsp impeded typical Chilo suppressalis larval development and induced high population reduction in vitro and in planta, implying the potential for further development as a new alternative field‐based approach of Chilo suppressalis control.